Criteria for Selecting Instructors of English for Academic Purposes Courses: What Do Students Look for? - John Harper; Shang Li (Yayasan Visi Intan Permata, 2021)
Seeking to provide insight into the role that English for Academic Purposes (EAP) courses play in China’s growing number of joint-venture universities (JVUs), this article reports on a study of the factors that motivate students’ selection of instructors for such courses. The study reports on three stages of the investigation: (1) a preliminary, online tapping of learners’ motives in EAP instructor selection, (2) a survey, based on the findings of Stage 1, in which past EAP students ranked qualities most and least desired of EAP instructors, (3) focus-group discussions (FGDs), based on the survey of Stage 2, in which past EAP students commented on the qualities that they most and least desired of EAP instructors. Survey results are grouped into the top three, bottom three, and middle three; survey results are analyzed in light of FGDs, with discrepancies between the two being acknowledged and interpreted. Three overarching pedagogical implications are presented: (1) the need of a sense of community in EAP courses, (2) the need of transparency in EAP courses, and (3) the perception of EAP instructors as first and foremost classroom teachers. Limitations of the study are duly noted.